Penggunaan Aplikasi Cerita Bergambar untuk Meningkatkan Kreativitas Menulis Siswa Sekolah Dasar - Rahmalia Ayu Isnaini; Ana Neneng Wahyuni; Ika Putra Viratama (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This research aims to explore the use of picture story applications in increasing students' writing creativity in elementary schools. By combining visual and narrative elements, this application is expected to stimulate students' imaginations and help them compose more creative stories. The method used in this research involves observation and analysis of students who use the application in the writing learning process. The research results showed that students who used the picture story application experienced significant improvements in their writing abilities, including in terms of creativity and writing structure. These findings indicate that picture story applications can be an effective tool in supporting the development of students' writing skills, as well as making a positive contribution to more interesting and innovative learning methods.